Fatigue and Fracture of Metals and Alloys Numerical and Experimental Study - Galkiewicz, Jaroslaw; Śnieżek, Lucjan; Lipiec, Sebastian (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue "Fatigue and Fracture of Metals and Alloys: Numerical and Experimental Study" includes 19 articles covering problems in fatigue and fracture mechanics from different parts of the scientific world. The issue includes articles presenting theoretical, numerical, statistical and experimental approaches to fatigue life estimation. The influence of technological processes, state of stress, or the environment on steel and aluminum alloys is presented. The subjects of the articles of interest, as they present solutions to common practical problems in the industry.